MALU DALAM AL-QUR’AN - Dina Uzlifatun Nada; Lailatul Rif’ah (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
The Holy Qur'an and sunnah have mentioned that the nature of shame (al-hayã) is the basic nature of akhlakul karimah that can encourage humans to do good and stay away from the prohibition of sharia, because 'shame' is concerned with self-esteem and honor. Shame is the main source of goodness and the element of glory in every work. Looking at the development of increasingly advanced times along with the development of today's technology, the phenomenon of moral collapse in society is increasingly rife. The urgency of planting an attitude of shame is expected to make every soul embedded in the nature of muraqabah, namely maintaining or feeling always supervised so as to form an attitude that is always wary of the Laws of God) and the nature of tajalli, namely if the soul is filled with ethical pearls and bodies that are accustomed to doing noble deeds, and realize the condition of a faithful, moral and civilized society. So here researchers use the study of shame in the Qur'an to study verses about the attitude of shame in the Qur'an and to find out how to cultivate shame in society. This approach in research uses a library research approach. Using this type of qualitative research. The method that researchers use is the thematic interpretation method, which is a way of interpreting the Qur'an by studying a certain theme and then collecting verses related to the verse that the researcher took. Then explained one by one from the nuzuli side, semantics, and interpretations are connected one verse with another verse so that it is collected to form a complete and comprehensive idea of the Qur'an's view of a theme studied. Some things that can cause a person to have a shy nature and this trait will be ingrained and grow in themselves, namely: staying away from habits caused by at least shame, strengthening faith and trust in the heart, forcing themselves to behave in shame recommended by religion.